Genomic Characterization Provides New Insights Into the Biosynthesis of the Secondary Metabolite Huperzine a in the Endophyte Colletotrichum gloeosporioides Cg01 - Kang, Xincong; Liu, Chichuan; Shen, Pengyuan; Hu, Liqin; Lin, Runmao; Ling, Jian; Xiong, Xingyao; Xie, Bingyan; Liu, Dongbo (Frontiers in Microbiology, 2019)
A reliable source of Huperzine A (HupA) meets an urgent need due to its wide use in Alzheimer’s disease treatment. In this study, we sequenced and characterized the whole genomes of two HupA-producing endophytes, Penicillium polonicum hy4 and Colletotrichum gloeosporioides Cg01, to clarify the mechanism of HupA biosynthesis. The whole genomes of hy4 and Cg01 were 33.92 Mb and 55.77 Mb, respectively. We compared the differentially expressed genes (DEGs) between the induced group (with added extracts of Huperzia serrata) and a control group. We focused on DEGs with similar expression patterns in hy4 and Cg01. The DEGs identified in GO (Gene ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) pathways were primarily located in carbon and nitrogen metabolism and nucleolus, ribosome, and rRNA processing. Furthermore, we analyzed the gene expression for HupA biosynthesis genes proposed in plants, which include lysine decarboxylase (LDC), copper amine oxidase (CAO), polyketides synthases (PKS), etc. Two LDCs, one CAO, and three PKSs in Cg01 were selected as prime candidates for further validation. We found that single candidate biosynthesis-gene knock-out did not influence the HupA production, while both LDC gene knock-out led to increased HupA production. These results reveal that HupA biosynthesis in endophytes might differ from that proposed in plants, and imply that the HupA-biosynthesis genes in endophytic fungi might co-evolve with the plant machinery rather than being acquired through horizontal gene transfer (HGT). Moreover, we analyzed the function of the differentially expressed epigenetic modification genes. HupA production of the histone acetyltransferase (HAT) deletion mutant △CgSAS-2 was not changed, while that of the histone methyltransferase (HMT) and histone deacetylase (HDAC) deletion mutants △CgClr4, △CgClr3, and △CgSir2-6 was reduced. Recovery of HupA-biosynthetic ability can be achieved by retro-complementation, demonstrating that HMT and HDACs associated with histone modification are involved in the regulation of HupA biosynthesis in endophytic fungi. This is the first report on epigenetic modification in high value secondary metabolite- producing endophytes. These findings shed new light on HupA biosynthesis and regulation in HupA-producing endophytes and are crucial for industrial production of HupA from fungi.